Factors Related to Gender Equality in Decision Making Following The Family Planning Program at BPS (Private Practice Midwife) Sri Rahayu, SST - Rosmiati, Rosmiati (STIKes RSPAD RSPAD Gatot Soebroto, 2023)
Decision making in reproductive health is not yet entirely in the hands of women. Often decisions are made based on husband or family factors. Thus, problems often occur with termination of pregnancy which can lead to death. The aim of this research is to look at factors related to gender equality in decision making to participate in the Family Planning Program at BPS Sri Rahayu, SST. The hypothesis that will be used is that there is a relationship between the independent variables Knowledge, Attitudes, perceptions and characteristics of husband and wife, namely Age, Occupation and Income, with the dependent variable, namely Gender Equality in decision making to take part in the Family Planning Program. The benefit of this research is that by knowing gender equality in decision making to participate in a family planning program, it is hoped that it can prevent unwanted pregnancies which will lead to a reduction in maternal mortality. Based on this, this research is quantitative research with a descriptive design using correlation studies (ex post facto), which aims to understand the relationship between the dependent and independent variables without researcher intervention. Judging from the time dimension, this research is a cross sectional study. Data were analyzed univariately and bivariately involving 96 mothers as respondents. The results of the research show that gender equality in the decision to take part in a family planning program is the highest among those who do not have gender equality in the decision to take part in a family planning program, totaling 54 mothers (56.3%) and the independent variables that have a significant relationship are Knowledge (p=0.000), P-value Attitude (p=0.000) P-value Perception (p=0.000) and for mother and father characteristics P-value for Father's Age (p=0.043), P-value for Mother and Father's Occupation (p=0.000), P-value for Family Income (p=0.000). The results of this research recommend to BPS Sri Rahayu, SST to increase promotion of gender equality. Recommendations are also given to other researchers who intend to conduct research on gender equality to involve more variables studied with different designs and use instruments that have standard validity and reliability values